Clinical Characteristics and Predictive Factors of Subclinical Diabetic Nephropathy - Zhang, Y.; Yang, J.; Zheng, M.; Wang, Y.; Ren, H.; Xu, Y.; Yang, Y.; Cheng, J.; Han, F.; Yang, X.; Chen, L.; Shan, C.; Chang, B. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Background: To investigate the clinical characteristics and predictive factors of subclinical diabetic nephropathy in type 2 diabetes patients.Methods: A total of 298 type 2 diabetes patients were divided into 3 groups based on 24-h urinary microalbumin and estimated glomerular filtration rate: patients with normal albuminuria and glomerular filtration rate (NC), patients with normoalbuminuria and glomerular hyperfiltration (SDN) and patients with microalbuminuria (EDN). The renal size, tubular injury markers and ambulatory blood pressure were analyzed.Results: Renal size increased in the SDN and EDN groups compared to the NC group (P<0.05), while renal length in the SDN group was greater than the EDN group (P<0.05). Patients in the SDN and EDN groups had higher level of urine retinol binding protein and N-acetyl-β-D-glucosaminidase and most of them developed proximal tubular dysfunction. The SDN group had higher 24-h mean and nocturnal diastolic blood pressure than the NC group (P<0.05), while the EDN group had higher systolic blood pressure and pulse pressure than the SDN group (P<0.01). More patients developed abnormal blood pressure rhythm in the SDN and EDN groups. The likelihood of a decrease in nocturnal systolic blood pressure was lower as the microalbuminuria increased. Increased renal size, more abnormal tubular injury markers and higher 24-h mean and nocturnal blood pressure were all risk factors of subclinical diabetic nephropathy.Conclusion: Patients with subclinical diabetic nephropathy had increased renal size, abnormal tubular injury markers, high blood pressure and abnormal circadian rhythm.
Keywords: ambulatory blood pressure; diabetic nephropathy; glomerular filtration rate; microalbuminuria; renal tubular injury markers